Transdiagnostic culturally adapted CBT with Farsi-speaking refugees: a pilot study. (24th November 2017) - Kananian, Schahryar; Ayoughi, Sarah; Farugie, Arieja; Hinton, Devon; Stangier, Ulrich
ABSTRACT: Background : Approximately half of all asylum seekers suffer from trauma-related disorders requiring treatment, among them Posttraumatic Stress Disorder (PTSD), depression, anxiety, and somatic symptoms. There is a lack of easily accessible, low-threshold treatments taking the cultural background into account. Culturally Adapted CBT (CA CBT) is a well evaluated, transdiagnostic group intervention for refugees, using psychoeducation, meditation, and Yoga-like exercises.Objective: An uncontrolled pilot study with male Farsi-speaking refugees from Afghanistan and Iran was conducted to investigate feasibility with this ethnic group; a group for which no previous CBT trials have been reported. Method : The participants were nine Farsi-speaking, male refugees with M.I.N.I./DSM-IV diagnoses comprising PTSD, major depressive disorder, and anxiety disorders. Treatment components were adapted to the specific cultural framework of perception of symptoms, causes, ideas of healing, and local therapeutic processes. Before and after 12 weeks of treatment, the primary outcome was assessed using the General Health Questionnaire (GHQ-28). Secondary outcome measures were the Posttraumatic Checklist, Patient Health Questionnaire, Somatic Symptom Scale, World Health Organization Quality of Life Questionnaire (WHOQOL-BREF), Affective Style Questionnaire (ASQ), and Emotion Regulation Scale (ERS). Results : Seven participants completed treatment. In the completer analysis, improvements were found on almost all questionnaires. Large effect sizes were seen for the GHQ-28 ( d = 2.0), WHOQOL-BREF scales ( d = 1.0–2.3), ASQ tolerating subscale ( d = 2.2), and ERS ( d = 1.7). With respect to feasibility, cultural adaptation seemed to be a crucial means to promote effectiveness. Conclusion : CA CBT may reduce general psychopathological distress and improve quality of life. Improvement in emotion regulation strategies may mediate treatment effects. More support should be provided to enhance coping with the uncertainty of asylum status and stressful housing conditions. CA CBT appears to be a promising transdiagnostic treatment, serving as an initial low-threshold therapy in a stepped care approach.